Research Progress of AΒ Targeted Therapy in Clinical Application of Alzheimer’s Disease - He, Shen (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Alzheimer’sdisease (AD) is a progressive neurodegenerative disease that poses a major health challenge to the aging global population. It is characterized by a progressive loss of cognitive functions, including memory, thinking, and behavioral abilities. Current literature shows that there is a critical gap in effective treatment options, as there are no widely accepted treatments that modify disease progression. This gap becomes increasingly important as the prevalence of AD increases. This article analyzes the application of Aβ-targeted therapy in AD, focuses on evaluating the impact of Lecanemab on cognitive function, and comprehensively evaluates the efficacy and safety of the treatment strategy. Study results show that Lecanemab can significantly reduce Aβ plaque burden and improve cognitive function in early-stage AD patients. The significance of this study is to provide a new direction for future AD treatment, and also points out safety issues that still need to be solved in current clinical practice. Future research can focus on improving the biological specificity of monoclonal antibodies and improving the safety of drugs to promote the development of AD treatment.